2011 IEEE RadarCon (RADAR) 2011
DOI: 10.1109/radar.2011.5960655
|View full text |Cite
|
Sign up to set email alerts
|

Range-Doppler domain signal processing to mitigate wind turbine clutter

Abstract: Wind turbines produce clutter signals that can bias estimates of the spectral moments and polarimetric variables of weather signals. These biases can propagate to and negatively influence the output of automatic algorithms, such as severe weather detection and quantitative precipitation estimates. Moreover, existing ground clutter filters are ineffective at removing wind turbine clutter (WTC) contamination because the moving components of the wind turbine produce clutter signals with nonzero Doppler frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Spacing of 7D (D as rotor diameter) is conventionally used by many current wind farms, but studies have shown that the optimal average spacing is considerably larger at 15D [17]. The increase of spacing will benefit WTC mitigation algorithms based on signal processing [10,11] because there will be more uncontaminated volumes in between contaminated ones, which will provide more accurate prior information about the weather estimates in the proximity of the wind farm area.…”
Section: Wind Turbine Spacingmentioning
confidence: 99%
See 1 more Smart Citation
“…Spacing of 7D (D as rotor diameter) is conventionally used by many current wind farms, but studies have shown that the optimal average spacing is considerably larger at 15D [17]. The increase of spacing will benefit WTC mitigation algorithms based on signal processing [10,11] because there will be more uncontaminated volumes in between contaminated ones, which will provide more accurate prior information about the weather estimates in the proximity of the wind farm area.…”
Section: Wind Turbine Spacingmentioning
confidence: 99%
“…The difficulty to separate wind turbine and weather return signal in both the spatial and Doppler domains has prompted ideas of combining information in both domains. Range-Doppler processing [10] exploits the difference between wind turbine and weather signals in the range-Doppler domain, alleviates Doppler spectral bins identified as WTC and reconstructs weather signal based on the spatial continuity assumption. The Adaptive Spectrum Processing (ASP) technique [11] makes use of the clustering nature of weather signals and adaptively constructs band pass filters for mitigation of WTC.…”
Section: Introductionmentioning
confidence: 99%
“…In (13), σ h is the RCS of the WT tower and can be calculated through (10) considering the segments found on the tower of the WT. In addition, mod(·,·) is the modulo operator which controls the unambiguous velocity range while the step function controls the signal level of the WTC considering the scattering properties of the blade, stationary part (i.e., tower) of the WT and DR values.…”
Section: Probabilistic Wtc Modellingmentioning
confidence: 99%
“…The transponder‐based detection method, which exploits a transponder to find the location of WTs, is found in [12]. Furthermore, additional WT detection efforts such as range‐Doppler imaging by using the radar raw data corresponding to the azimuthal sector that WTs are located in [13], adaptive clutter mapping via averaging multiple radar‐scan data [14] and disposition of the radial velocity characteristics of WT and meteorological data [15] have been introduced. The literature also introduces a few design proposals that focus on the mitigation of WTC effects on radar signals.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [20] proposed an algorithm which detects the WTC contamination in spotlight mode and uses interpolation to reduce the bias in reflectivity and radial velocity estimates; however, this suffers from the same problems as the previously mentioned algorithms. Recently, an algorithm based on edge detection was proposed in [21]. This algorithm exploits the spatial discontinuity of the WTC signal in the range-Doppler spectrum (RDS).…”
Section: Introductionmentioning
confidence: 99%